2006
DOI: 10.1073/pnas.0602827103
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic analysis of the “ECE” (CYC/TB1) clade reveals duplications predating the core eudicots

Abstract: Flower symmetry is of special interest in understanding angiosperm evolution and ecology. Evidence from the Antirrhineae (snapdragon and relatives) indicates that several TCP gene-family transcription factors, especially CYCLOIDEA (CYC) and DICHO-TOMA (DICH), play a role in specifying dorsal identity in the corolla and androecium of monosymmetric (bilateral) flowers. Studies of rosid and asterid angiosperms suggest that orthologous TCP genes may be important in dorsal identity, but there has been no broad phyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
264
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 195 publications
(277 citation statements)
references
References 53 publications
13
264
0
Order By: Relevance
“…The greater genetic similarity within rather than among these groups suggests that many functionally important duplication events in the ECE gene subfamily occurred after the divergence of the Lamiales, Fabales, and Asteraceae lineages, respectively. The results of Howarth and Donoghue (16) are similar in this respect in that groupings within subclades CYC1, CYC2, and CYC3 are largely consistent with organismal phylogeny. Given this concurrence, we tested the phylogenetic distribution of our gene data when combined with many of the less-complete Dipsacales and Asterales sequences published by the former authors, and all well supported relationships were consistent with the results reported here (data not shown).…”
Section: Resultssupporting
confidence: 54%
See 2 more Smart Citations
“…The greater genetic similarity within rather than among these groups suggests that many functionally important duplication events in the ECE gene subfamily occurred after the divergence of the Lamiales, Fabales, and Asteraceae lineages, respectively. The results of Howarth and Donoghue (16) are similar in this respect in that groupings within subclades CYC1, CYC2, and CYC3 are largely consistent with organismal phylogeny. Given this concurrence, we tested the phylogenetic distribution of our gene data when combined with many of the less-complete Dipsacales and Asterales sequences published by the former authors, and all well supported relationships were consistent with the results reported here (data not shown).…”
Section: Resultssupporting
confidence: 54%
“…In Gerbera ray flowers, the expression of GhCYC2 was specifically excluded from the dorsal rudimentary petals, suggesting functional deviation from Lamiales and Fabaceae. A similarly ventral expression pattern was documented for a CYC3-subclade gene from Lonicera (Dipsacales), whereas a CYC2-subclade gene expressed dorsally (16). However, preliminary phylogenetic analyses including some of these authors' shorter sequences suggest that GhCYC2 belongs to the CYC2 subclade (data not shown).…”
Section: Ghcyc2 Expression Is Primarily Ventral and Correlates With Omentioning
confidence: 63%
See 1 more Smart Citation
“…CYC and DICH encode proteins belonging to the plant-specific TEOSINTE BRANCHED1, CYCLOIDEA, and PCF (TCP) family of transcription factors (Cubas et al, 1999). Based on the TCP domain, members of the TCP family are classified into PCF (TCP-P or class I) and CYC/TB1 (TCP-C or class II) subfamilies (Cubas et al, 1999;Navaud et al, 2007), and the latter is further divided into CIN and ECE lineages (Howarth and Donoghue, 2006). Phylogenetic analyses show that two major duplication events within the ECE lineage took place just before the radiation of core eudicots; these duplication events gave rise to three clades, CYC1, CYC2, and CYC3 (Howarth and Donoghue, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Based on the TCP domain, members of the TCP family are classified into PCF (TCP-P or class I) and CYC/TB1 (TCP-C or class II) subfamilies (Cubas et al, 1999;Navaud et al, 2007), and the latter is further divided into CIN and ECE lineages (Howarth and Donoghue, 2006). Phylogenetic analyses show that two major duplication events within the ECE lineage took place just before the radiation of core eudicots; these duplication events gave rise to three clades, CYC1, CYC2, and CYC3 (Howarth and Donoghue, 2006). Increasing evidence indicates that CYC2 clade genes, specific for the core eudicots, were repeatedly recruited to function in the control of floral zygomorphy based on their strong, dorsoventrally asymmetric expression (Luo et al, 1996(Luo et al, , 1999Feng et al, 2006;Zachgo, 2007, 2009;Broholm et al, 2008;Gao et al, 2008;Kim et al, 2008;Wang et al, 2008Wang et al, , 2010Preston and Hileman, 2009;Song et al, 2009;Zhang et al, 2010;Howarth et al, 2011).…”
Section: Introductionmentioning
confidence: 99%